Buddhism, Sustainability and Organizational Practices Fertile Ground?* - Abeydeera, S.; Kearins, K.; Tregidga, H. (Greenleaf Publishing, 2016)
This paper provides a systematic review of literature relating to Buddhism, sustainability and organizational practices. How extant literature acknowledges Buddhism informing sustainability as an alternative to current business practices predominantly governed by an economic rationale is examined. Thirty journal articles and 20 books/book chapters are analyzed. Commonly discussed Buddhist principles in the literature include the Four Noble Truths, the Noble Eightfold Path, the Law of Karma, and Compassion. Through the analysis of Buddhist principles, a set of values are derived that enable the possibility of fostering sustainability in organizations. Core values emphasized are interconnectedness, moderation and empathy. Given the limited attention to date, this paper contributes to the extant literature through providing avenues for future research that could examine efforts to enact these core values in further exploring the connections between Buddhism, sustainability and organizational practices.
Keywords: Buddhism; Sustainability; Organizational Practices